Depression and quality of life in hemodialysis andpredialysis patients in a sample from Turkey - SAYAR, MUSTAFA KEMAL; YANARTAŞ, ÖMER (My University, 2016)
In this study, we aimed to examine the quality of life, depression, and anxiety in chronic renal failure at the predialysis and hemodialysis stage and groups, to show that depression anxiety start prior to dialysis, and to explore the impact of depression and anxiety on the quality of life of these patients. We included 49 hemodialysis and 50 predialysis (stage IV chronic kidney failure) patients who were followed up at the Bakırkoy Dr. Sadi Konuk Training and Research Hospital‘s Dialysis Unit and Nephrology Outpatient Clinic. Sociodemographic data were obtained from all patients in addition to the Hospital Anxiety and Depression Scale and the MOS 36-Item Short-Form Health Survey (SF-36). Results: No significant differences were found in terms of sociodemographic characteristics of two study groups. No significant differences were found in terms of HADS scores of two study groups SF-36 scores were not significantly different except for pain and physical function subscale scores. Quality of life component scores were found significantly lower in depression risk group based on HADS scores, regardless of renal failure stages. Our findings revealed that the quality of life levels were similar in both predialysis and dialysis patients. Depression and anxiety were determinant of quality of life, regardless of the stage of the kidney disease. Since the quality of life in patients with chronic renal failure was considered to be an important factor that determines mortality and morbidity, the treatment of depression at all stages of the illness is gaining importance. Psychiatric examination, psychoeducation and treatment of depression and anxiety symptoms would facilitate psychosocial adjustment and improve patient‘s coping skills prior to developing end-stage renal failure and lower the mortality and morbidity rates in these patients.
Keywords: Hemodialysis; Predialysis; Depression; Quality of Life; Mortality; Morbidity